1994
DOI: 10.1152/jn.1994.71.3.1174
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of a slowly inactivating potassium current to the transition to firing of neostriatal spiny projection neurons

Abstract: 1. Neostriatal spiny projection neurons display a prominent slowly depolarizing (ramp) potential and long latency to spike discharge in response to intracellular current pulses. The contribution of a slowly inactivating A-current (IAs) to this delayed excitation was investigated in a neostriatal slice preparation using current pulse protocols incorporating information based on the known voltage dependence, kinetics, and pharmacological properties of IAs. 2. Depolarizing intracellular current pulses evoked a sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
156
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(179 citation statements)
references
References 0 publications
23
156
0
Order By: Relevance
“…Thus, it can be concluded that the 4-AP-induced EEG discharges are the result of an increment in frequency firing, combined with an increased excitatory glutamate-and GABA-mediated synaptic transmission. Consistent with this conclusion, it has been found that dendrotoxins, like 4-AP, induce increased neuronal firing (Nisenbaum et al, 1994) and are also potent convulsants (Gandolfo et al, 1989;Bagetta et al, 1992).…”
Section: Glutamate Release Andsupporting
confidence: 63%
See 1 more Smart Citation
“…Thus, it can be concluded that the 4-AP-induced EEG discharges are the result of an increment in frequency firing, combined with an increased excitatory glutamate-and GABA-mediated synaptic transmission. Consistent with this conclusion, it has been found that dendrotoxins, like 4-AP, induce increased neuronal firing (Nisenbaum et al, 1994) and are also potent convulsants (Gandolfo et al, 1989;Bagetta et al, 1992).…”
Section: Glutamate Release Andsupporting
confidence: 63%
“…of neuronal firing (Bargas et al, 1989;Nisenbaum et al, 1994;Koyano et al, 1996). Thus, it can be concluded that the 4-AP-induced EEG discharges are the result of an increment in frequency firing, combined with an increased excitatory glutamate-and GABA-mediated synaptic transmission.…”
Section: Glutamate Release Andmentioning
confidence: 97%
“…As mentioned above, another major current that operates in the membrane voltage range just subthreshold to spike firing is a 4-aminopyridine-and dendrotoxin-sensitive slowly inactivating K Ï© conductance (Storm 1988;Hammond and CrĂ©pel 1992;Nisenbaum et al 1994Nisenbaum et al , 1996. This slow outward K Ï© current is responsible for membrane outward rectification in the depolarized voltage range and functionally opposes the sustained membrane depolarization mediated by the I NaP current to prevent PFC neurons from reaching firing threshold (Yang et al 1996a).…”
Section: Ionic Mechanisms That Regulate Spike Firing Threshold In Pfcmentioning
confidence: 98%
“…Medium spiny neurons fire with a maximal firing rate y max of about 6 Spikes per 100 msec (Apicella et al, 1992;Pineda et al, 1992;Nisenbaum et al 1994). A factor a = 0.3 Spikes/(100 msec * mV) is used to scale the firing rate to experimental data and is estimated from firing rates for constant current injections in the absence of dopamine agonists (estimated from figure 1 in Nisenbaum et al 1994; similar in figure 3 in Pineda et al, 1992). Eq.…”
Section: Modelmentioning
confidence: 99%